Identification of proteins and genes as potential biomarkers in brown-marbled grouper (Epinephelus fuscoguttatus forsskal) resistance to Vibrio sp - Low, Chen Fei (2014)
The gram-negative marine bacterium, Vibrio sp. has frequently been identified as the causative pathogen responsible for the infectious disease vibriosis in the marine aquaculture industry. This disease is one of the majorc allenges facing brown-marbled grouper aquaculture, causing fish farmers globally to suffer substantial economic losses. In this study, several experiments were conducted using a range of methodologies to identify proteins and genes that are immune response-related upon Vibrio infection in brown-marbled grouper. Serum proteome profiles from two-dimensional gel electrophoresis were compared between infected grouper and control grouper after 4 hours of pathogen challenge. Differentially expressed proteins were then identified by MALDI TOF. The serum proteins that were ,ighly expressed during early Vibrio infection of grouper were putative apolipoprotein A-I, natural killer cell enhancement factor and lysozyme g.The transcriptome of brown-marbled grouper spleen was studied by RNAsequencing using Next Generation Sequencing technology. Gene expression in grouper spleen was compared between the infected grouper and control grouper. A total of 4162 unigenes were up-regulated in infected grouper, and 4988 unigenes were down-regulated. Gene ontology classification showed 338 differentially expressed genes were involved in immune system processes. Cell killing and antioxidant activity class have highest percentage of differentially expressed unigene of 34.48% and 37.74% respectively. Upregulated unigenes in the cell killing class included transporter-associated with antigen processing 2, and cytotoxic and regulatory T cell protein. KEGG pathway annotation identified eight immune-related pathways and also seven non-immune response-related pathways that were significantly enriched in differentially expressed genes. Among the most abundantly upregulated unigenes, four unigenes were found to be novel and were not annotated in any of the database. These novel unigenes warrant further identification and characterization of its function in immune response of grouper against pathogens. Lastly, brown marbled grouper fingerlings observed for seven days after experimental infection with Vibrio parahaemolyticus determined grouper susceptible to infection, with these fish having skin lesions ≥ 5mm. Grouper that were resistant to infection had no observable skin lesion. Skin lesion specimens observed under the scanning electron microscope revealed disintegration of skin around the lesion, and presence of bacterial cells under high magnification of 6000X. Serum proteome profiles were compared between the resistant and susceptible grouper by two-dimensional gel electrophoresis. Putative parvalbumin beta-2 subunit I, alpha-2-macroglobulin, nattectin and immunoglobulin light chain were identified to be differentially expressed in resistant grouper. In summary, resistance of grouper to bacterial infection involved complex mechanisms consisting of different pathways with distinct methods of activation and regulation. Genes and proteins altered in these pathways are potential markers to identify Vibrio resistant grouper as well as targets for immunomodulation and disease prevention through vaccination. It could that putative parvalbumin beta-2 subunit I, alpha-2-macroglobulin, nattectin and immunoglobulin light chain are among the important proteins participating critically in disease resistance mechanism in grouper, which are over-expressed to function collectively, thus contributing to the resistance of grouper to V. parahaemolyticus infection.